(3GdehGYX GdHGdZIs - (3eMeO Hf YHO GdhgGH Hf OGhO GdgeOGfj GdcGXej EeGe GdMQejf,J (B1305 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Pj Gdeff hGdBdGA GdSGHZI hGdUdGI hGdSdGe Ydi GdTeS GdHGRZI eMeO UGMH GdehGYX GdfGHZI s
(3BNQgG (B:s
(3aj cd efRd ef gPg GdefGRd hdjcf gPG BNQ eG ofedjg aj GdLRA GdChd ef gPG GdcJGH s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B268s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs